Prevalence of Chlamydia infection among asymptomatic female commercial sex workers in the Kumasi Metropolis - Abubakari, Amina (2011)
A Thesis Submitted to the Department of Clinical Microbiology, College of Allied health Sciences, Kwame Nkrumah University of Science and Technology (KNUST), Kumasi in partial fulfillment of the requirement of the award of Master of Science degree in Clinical Microbiology.